Historical Context of Environmental Education in the Amazon: a bibliographic review - Barbosa, Manuel Saldanha; Lima, Renato Abreu (Revista Cerrados, 2023)
The concern of scientists, educators, philosophers, poets and observers regarding man's distancing from nature dates back many centuries. In this sense, this work aimed to analyze the historical context of Environmental Education in Amazonas from 2008 to 2021, through a bibliographical review tracing the relevant points in this process, which contributed to the strengthening of EE in recent years. For data collection, the SCIELO, Google Academic, Google Scholar, Capes and Plataforma Sucupira databases were used, language was not limited in an attempt to obtain a relevant amount of theoretical reference, for data collection, information provided and disclosed without consider the period of publication. An average of 43 scientific works were found, including articles, dissertations and theses, of which only 20 were selected according to the inclusion and exclusion criteria. Of these works, all were published in Portuguese. With regard to Environmental Education in Amazonas, there is an urgent need for it to be participatory, transformative and emancipatory, in search of the transition from naive consciousness to critical consciousness. And for praxis to occur (reflection-action), the generating themes, proposed by Freire, can meet the confrontation of the society/culture and nature dichotomy and, in this sense, implement the attributes of EE in a Critical-Transforming perspective.